Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1088/1755-1315/146/1/012028
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Antibiotics in Water in Xiaodian Sewage Irrigation Area, Northern China

Abstract: Abstract. The Xiaodian sewage irrigation area in northern China has a long history of sewage irrigation. The surface water and groundwater samples were collected and analyzed in this region. All the 25 kinds of antibiotics have been detected in the surface water in this study area. The order of average detection frequency is Macrolides (MLs, 98.2%) > Fluoroquinolones (FQs, 91.3%) > Tetracyclines (TCs, 87.5%) > Sulfonamides (SMs, 75.0%). The sample with the highest concentration of antibiotics (730.19 ng/L) is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
0
1
0
Order By: Relevance
“…Similar research from the Xiaodian Wastewater of Irrigation Area of Northern China found 15 antibiotics in groundwater samples, with antibiotic concentrations ranging from 2.75 to 114.38 ng/L (Li, Dong, Hu, & Wang, 2018). The issue of antibiotics pollution extends to Cluj-Napoca in Romania and its surrounding areas, which are near urban sites that are susceptible to seepage from municipal solid waste landfills, urban and hospital wastewater, as well as other agricultural activities.…”
Section: Pharmaceutical Contamination Of Groundwatermentioning
confidence: 72%
“…Similar research from the Xiaodian Wastewater of Irrigation Area of Northern China found 15 antibiotics in groundwater samples, with antibiotic concentrations ranging from 2.75 to 114.38 ng/L (Li, Dong, Hu, & Wang, 2018). The issue of antibiotics pollution extends to Cluj-Napoca in Romania and its surrounding areas, which are near urban sites that are susceptible to seepage from municipal solid waste landfills, urban and hospital wastewater, as well as other agricultural activities.…”
Section: Pharmaceutical Contamination Of Groundwatermentioning
confidence: 72%
“…Among these pathways, sewage irrigation has received a great deal of attention. At present, 15 antibiotics have been detected in the sewage irrigation area of Taiyuan, with a maximum concentration of 114.38 ng/L [74]. Studies have shown that sewage irrigation has input more types and quantities of antibiotics into groundwater than groundwater irrigation [75].…”
Section: Agriculture Livestock Production and Aquaculturementioning
confidence: 99%